2014
DOI: 10.1364/ol.39.002086
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing spatial resolution in digital holographic microscopy by biprism structured illumination

Abstract: A novel and efficient architecture of a structured-illumination digital holographic microscope (DHM) is presented. As the DHM operates at the diffraction limit, its spatial resolution on label-free imaging of transparent samples is improved by illuminating the sample with a structured illumination produced by a Fresnel's biprism. The theoretical analysis of the method forecasts a twofold improvement of the spatial resolution. The proposed method requires only two images to improve the spatial resolution, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Applications of this have included quantitative measurements of whole-cell morphology and mass, spectroscopy, hemoglobin concentration, etc [8][9][10]. Previous work that considered SI's capabilities to augment the effectiveness and accuracy of these applications has utilized SI for subdiffraction resolution imaging of coherent scatter and optical phase-delays [17,[37][38][39][40]. To the best of our knowledge, this work reports one of the earliest examples of applying the SI framework for extracting 3D biological RI, the intrinsic optical property that determines the object's scattering and phase-delay characteristics [41].…”
Section: Discussionmentioning
confidence: 99%
“…Applications of this have included quantitative measurements of whole-cell morphology and mass, spectroscopy, hemoglobin concentration, etc [8][9][10]. Previous work that considered SI's capabilities to augment the effectiveness and accuracy of these applications has utilized SI for subdiffraction resolution imaging of coherent scatter and optical phase-delays [17,[37][38][39][40]. To the best of our knowledge, this work reports one of the earliest examples of applying the SI framework for extracting 3D biological RI, the intrinsic optical property that determines the object's scattering and phase-delay characteristics [41].…”
Section: Discussionmentioning
confidence: 99%
“…Previous works, however, have demonstrated that structured illumination (SI) microscopy, already an established imaging technique for fluorescent super-resolution [29][30][31][32][33][34], has considerable utility as a SA technique when operated in the coherent imaging realm. Such studies have demonstrated SI's coherent sub-diffraction resolution imaging capabilities for visualizing 2D and 3D scattering/quantitative-phase (QP), as endogenous contrast mechanisms [35][36][37][38][39][40][41][42][43]. Hence, SI fills a niche role as a sub-diffraction resolution imaging solution suitable for studies probing molecular and biophysical/biochemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…The lateral resolution is related with the wavelength and the MO's numerical aperture. Therefore, the synthetic aperture method [39][40][41][42][43] and structured illumination approach [44][45][46][47] are utilized to enhance the resolution when the wavelength remains unchanged. In addition, when the specimen's depth change is larger than the optical path of a wavelength, the phase unwrapping algorithms are adopted to obtain the real phase for 2π ambiguity problem [48][49][50], in which multi-wavelength phase unwrapping methods permit larger synthetic wavelengths to unwrap [51][52][53].…”
Section: Introductionmentioning
confidence: 99%